Evaluation of serum Spondin 2 levels in the different stages of Type 2 diabetic nephropathy. (October 2015) - Kahvecioglu, Serdar; Guclu, Metin; Ustundag, Yasemin; Gul, Cuma Bulent; Dogan, Ibrahim; Dagel, Tuncay; Esen, Bennur; Akturk Esen, Selin; Celik, Huseyin; Esen, Irfan
Abstract: Aim: We aimed to determine whether serum SPON2 is a useful biomarker in the detection of Diabetic Nephropathy (DN) and to compare serum SPON2 levels with 24‐hour urinary albumin excretion rate (UAER) in patients with DN at different stages. Methods: The cohort included 80 adult patients with T2D and 20 healthy controls. The patients with T2D were divided into four groups according to UAER and serum creatinine (sCr) levels. Group 1 consisted of patients with normoalbuminuria (n = 20), Group 2 with microalbuminuria (n = 20), Group 3 with macroalbuminuria (n = 20) and Group 4 with albuminuria and sCr > 1.5 mg/dL (n = 20). Results: There were no significant differences between the groups in terms of demographic data, C‐reactive protein, HbA1c, lipids, serum uric acid levels and leukocyte counts. SPON2 levels were observed to increase linearly with increasing severity of diabetic nephropathy levels. The SPON2 levels of Group 4 were significantly higher than Group 1 and the controls, and SPON2 levels of Group 3 were significantly higher than Group 1. Blood urea nitrogen, creatinine and UAER were significantly positively correlated with SPON2; serum total protein and calcium levels were negatively correlated with SPON2 in patients with DN. Conclusion: We observed a linear and significant increase in SPON2 levels of patients with T2D as the stage of DN increased, but serum SPON2 level was not as effective as microalbuminuria in reflecting nephropathy. Also, serum SPON2 level was not as good as urine and tissue levels of SPON2 in detection of renal damage in DN. Summary at a Glance: This study highlights the challenges in developing better biomarkers for the assessment of disease progression in diabetic kidney disease. The cohort examines the role of serum spondin‐2 as a marker of disease progression diabetic nephropathy.